PENGARUH RIGOROUS MATHEMATICAL THINKING TERHADAP KEMAMPUAN LITERASI MATEMATIKA SISWA KELAS VII SMP N 2 KOTA BENGKULU - Gyzka Veliesa; Saleh Haji; Hari Sumardi (Jurnal Lebesgue : Jurnal Ilmiah Pendidikan Matematika, Matematika dan Statistika, 2023)
This study aims to determine the effect of the Rigorous Mathematical Thinking learning on Students' Mathematical Literacy ability. This type of research uses the Quasi Experiment method. Data collection is done through tests. Data analysis used the Ancova test. The sample of this study were students of SMA Negeri 2 Bengkulu City in class VII I and VII K. The results showed that: (1) there was a linear covariate effect of initial ability on students' mathematical literacy abilities with an effect of 26,5%, (2) there was an effect of Rigorous Mathematical Thinking learning on students' mathematical literacy abilities with an effect of 62,6%, and (3) there was a higher mathematical literacy abilities achievement for class VII students of SMP Negeri 2 Bengkulu City who are taught using Rigorous Mathematical Thinking learning compared to classes taught with conventional learning